The role of employee magazines as an internal communication tool in international organisations (Case of Automotive Industry in Germany and South Africa) - Grabuschnig, Miriam; Vizgirdaitė, Jurgita (Information & Media, 2016)
The purpose of this paper is to develop a model for employee magazines depicting organizational culture in international companies working across borders. Employee magazines are part of the internal communication mix. The main objectives of internal communications in general and employee magazines in particular are to inform the employees (rational factors) and help building a community among them (emotional factors). The model presented in the paper includes three levels: the universal factors, which should be part of every employee magazine, the culture-specific level, where the world is divided into six parts and a third country-specific level, which includes the relevant factors in one specific country based on Hofstede’s cultural dimensions. In the paper Germany and South Africa are chosen for the third level. In order to test the usability of the model and make recommendations for one company, the employee magazines of Volkswagen Germany and Volkswagen South Africa are analysed on all three levels.